Identification of Website and Instagram as Digital Marketing Voyaz - Rizki Nurul Nugraha; Lisa Sarinah (West Science Interdisciplinary Studies, 2024)
Digital marketing is one of the strategies that are widely used by companies today. Digital-based marketing helps companies in promoting products or services, building brand image, and helping to interact with consumers. For example, by utilizing websites and social media platforms such as Instagram, Facebook, X / Twitter, and many more. Voyaz is a travel agent that provides travel planning services. The company utilizes the website and Instagram as their marketing media. This type of research is qualitative, with the analysis method used is descriptive qualitative. Data collection is done by observing and taking data from the website and Instagra Voyaz. The purpose of this study is to identify the digital marketing strategy implemented by Voyaz, as well as provide recommendations for further improvement and development. The results showed that digital marketing through Voyaz website and Instagram was quite good. However, there are several obstacles that need to be considered such as some website displays that cannot be accessed information, at least posting promotional photos / videos on Instagram. Voyaz needs to improve the performance of their website and post more promotional photos/videos on Instagram.